A Case Report on Successful Management of Recurrent Pregnancy Loss through Ayurveda - K O, Nanda; G I, Sathish; Bevur, Spoorthi Sanjaya (Journal of Neonatal Surgery, 2025)
Introduction: Infertility is defined as the inability to achieve a successful pregnancy after 12 months or more of regular, unprotected intercourse1. PCOS is a heterogenous endocrinal disorder which majorly contributes to infertility for the ovarian factor. Recurrent Pregnancy Loss (RPL), defined as the loss of two or more consecutive pregnancies before the 20th week of gestation2. This paper discusses a successful case report of infertility due to PCOS and recurrent pregnancy loss (RPL), highlighting its management through Ayurvedic therapies. Case report: 28 years old women presented with irregular menstrual cycle with a history of five consecutive early pregnancy losses (6-8 weeks) within the last 4 years of married life. On evaluation diagnosed as PCOS with TORCH infection positive for Cytomegalovirus and Rubella infections during her second pregnancy even after treatment for the same she ends up with next 3 consecutive miscarriage. Treatment protocol was planned considering the principles of Garbhasravi Vandhyatwa i.e., Virechana, Uttarabasti and Shamana Chikitsa. Results: The patient conceived after the 2 courses of Ayurvedic treatment and regular follow-up, she delivered a healthy Male baby boy.